2018
DOI: 10.3389/fimmu.2018.02229
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of TRIM28 Enhances the Expression of IFN-β and Proinflammatory Cytokines During HPAIV Infection of Human Lung Epithelial Cells

Abstract: Human infection with highly pathogenic avian influenza viruses (HPAIV) is often associated with severe tissue damage due to hyperinduction of interferons and proinflammatory cytokines. The reasons for this excessive cytokine expression are still incompletely understood, which has hampered the development of efficient immunomodulatory treatment options. The host protein TRIM28 associates to the promoter regions of over 13,000 genes and is recognized as a genomic corepressor and negative immune regulator. TRIM28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 75 publications
1
88
0
Order By: Relevance
“…The SUMOylation deficient TRIM28 can stimulate and prime IFN-α mediated innate immune defenses and restrict influenza A virus replication via a JAK1-dependent pathway [41]. Meanwhile, phosphorylation of TRIM28 leads to increased expression level of IFN-β in human lung epithelial cells during infection with highly pathogenic avian influenza viruses [42]. Knockdown of TRIM28 in A549 cells increased Sendai virus-induced IFN-α production and weakened IFN-sensitive vesicular stomatitis virus infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…The SUMOylation deficient TRIM28 can stimulate and prime IFN-α mediated innate immune defenses and restrict influenza A virus replication via a JAK1-dependent pathway [41]. Meanwhile, phosphorylation of TRIM28 leads to increased expression level of IFN-β in human lung epithelial cells during infection with highly pathogenic avian influenza viruses [42]. Knockdown of TRIM28 in A549 cells increased Sendai virus-induced IFN-α production and weakened IFN-sensitive vesicular stomatitis virus infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…PKR activation may not always be beneficial. Different strains of influenza vary in their ability to activate or evade the ISR [55,56]. Some highly pathogenic avian influenza viruses (e.g.…”
Section: Influenzamentioning
confidence: 99%
“…Some highly pathogenic avian influenza viruses (e.g. H5N1, H7N7 and H7N9) induce severe pulmonary inflammation owing to excessive production of IFN-β, interleukin (IL)-6 and IL-8 [55]. This response appears to be mediated by PKR triggering a cascade that leads to phosphorylation of TRIM28, a regulator of many immunomodulatory genes.…”
Section: Influenzamentioning
confidence: 99%
“…Recently, a new mechanism by which MAPK p38 affects dysregulation of cytokine induction was unraveled, deciphering an IV strain-specific phosphorylation of transcriptional repressor TRIM28 (tripartite motif-containing 28) at S473, which is induced by a signaling cascade constituted of protein kinase R (PKR), p38 MAPK and MSK1 in response to RIG-I-independent sensing of viral 5 0 PPP RNA. By using chemical inhibitors as well as knockout cell lines, it was shown that MAPK p38-dependent phosphorylation of TRIM28 facilitates a functional switch leading to increased cytokine levels in cells infected with highly pathogenic viruses (Krischuns et al 2018). Besides its role in the induction of pro-inflammatory and antiviral cytokines, there have been reports of a virus-supportive function of MAPK p38 observed after inhibition of the pathway with different p38 inhibitors (Marchant et al 2010;Choi et al 2016;McCaskill et al 2017).…”
Section: Stress-induced Mapks Jnk and P38mentioning
confidence: 99%